Analysis of Career Development Programs and Employee Work Motivation in Madiun Institutions - Erika Sari Yulianti; Satrijo Budiwibowo; Elly Astuti (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2021)
This study aims to determine the HR development program of employees through career development, motivation. This study uses a qualitative descriptive research Case Study with eight respondents, namely: Head of Agency, Head of Formation, Development and Administration of Personnel, Head of Education and Training, Head of Staff Mutation, and four Employees. The results of this study are that career development programs and systems implemented in 2018 are good enough but not perfect because they do not have a clear pattern that still follows the merits system of the government, and motivation can be said to be good because there are rewards to employees and relationships between employees conducive